2023
DOI: 10.4103/1673-5374.355742
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IgLON5 disease: a novel topic beyond neuroimmunology

Abstract: Anti-IgLON5 disease is a recently defined autoimmune disorder of the nervous system associated with autoantibodies against IgLON5. Given its broad clinical spectrum and extremely complex pathogenesis, as well as difficulties in its early diagnosis and treatment, anti-IgLON5 disease has become the subject of considerable research attention in the field of neuroimmunology. Anti-IgLON5 disease has characteristics of both autoimmunity and neurodegeneration due to the unique activity of the anti-IgLON5 antibody. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…(1) It has been firstly observed that anti-IgLON5 antibodies can cause relatively long-lasting effects, with motor impairment persisting for 3 months in passive transfer animal models. (2) The motor impairment associated with anti-IgLON5 antibodies may be related to the nigrostriatal dopaminergic pathway. (3) The deposition of p-Tau has been observed in vivo for the first time, indicating long-term exposure to anti-IgLON5 antibodies can lead to neurodegenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…(1) It has been firstly observed that anti-IgLON5 antibodies can cause relatively long-lasting effects, with motor impairment persisting for 3 months in passive transfer animal models. (2) The motor impairment associated with anti-IgLON5 antibodies may be related to the nigrostriatal dopaminergic pathway. (3) The deposition of p-Tau has been observed in vivo for the first time, indicating long-term exposure to anti-IgLON5 antibodies can lead to neurodegenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…No specific cutoff values have been established as positivity of these Abs is not expected in the general population. The relatively low titers detected in our patient may be explained by the early stage of the disease as an Abs titer is expected to increase as the disease progresses ( 28 , 29 ). There are also significant associations between certain haplotypes and anti-IgLON5 disease, indicating a specific genetic susceptibility to the disease.…”
Section: Discussionmentioning
confidence: 79%
“…Anti-IgLON5 encephalitis is a rare neurological entity that combines autoimmunization with neurodegeneration, which has heterogenous manifestations such as sleep disorder, gait abnormality, bulbar symptoms, as well as cognitive impairment, with or without chorea [ 2 , 3 ]. Most commonly, this disease is diagnosed among elderly patients with no sex predominance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%